ANALISIS PENGARUH KOMPENSASI, MOTIVASI, LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DENGAN KOMITMEN ORGANISASIONAL SEBAGAI VARIABEL INTERVENING - Dewi Shanty; Sekar Mayangsari (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2017)
This study is purposed to analyze the performance of employees in the fields of accounting, finance, tax, audit. The analysis data technique in this study using SEM analysis. The results of this study show that compensation, motivation not significant influence organization commitment, work environment positive significant influence organization commitment, compensation not negative influence employee performance, motivation not significant influence employee performance, work environment positive significant influence employee performance, organization commitment not significant influence employee performance, organizational commitment not able mediate the relationship between compensation, motivation, work environment and employee performance.